If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 * 2y + -5y = -4 Multiply 2 * 2 4y + -5y = -4 Combine like terms: 4y + -5y = -1y -1y = -4 Solving -1y = -4 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '-1'. y = 4 Simplifying y = 4
| (x-3)-(x+2)=6x | | 1x+1y=9 | | b^3=16b | | 8x-34=32+23x | | 7w+17=10 | | 3(5-3x)-2(5+2x)=3(x+1)-6x-23 | | 40=5x+3x+8 | | 8m^3-162m=0 | | -12=3v+10 | | 16=7x+12 | | 2x-3x=6x | | (5p+1)(p+5)=0 | | y+64=11 | | -6a=2 | | 5x+43=9x+6 | | 94=6x+6x+10 | | 7(b-2a)=5(-3a+1) | | 5m+9=3(m-6)+7 | | y+60=11 | | 0.7x+0.6=-0.8 | | y+6-1=11 | | 14(x-y)=336 | | 3x-7+x=2x-9 | | 67x+8=41+21x | | 12(x+y)=336 | | 2(x+4)=x+6 | | 6u=5u-8 | | 6+3x=1x | | 5=4x+6x+5 | | 10=-6k+k | | -6=-2n | | 5(3-2x)-3(4-2x)=19 |